Cultivo de Pleurotus Sajor-Caju (FR.) Singer em resíduos de Siagrus Oleracea (MART.) BECC, com suplementação alternativa no sul do Tocantins - Menezes, Ana Cristina de (Universidade Federal do Tocantins, 2022)
Lignocellulosic residues, composed of lignin, hemicellulose and cellulose, are important environmental pollutants. The forestry and agricultural industries generate a large amount of materials, which can be easily broken down by lignocellulosic enzymes. Mushrooms of the genus Pleurotus secrete specialized enzymes to degrade lignin, cellulose and hemicellulose, and have been extensively studied because they are easy to grow when compared to other edible species and because of their nutritional and nutraceutical properties. The objective of this study was to verify the viability of production of Pleurotus sajor-caju, under rustic conditions - room adapted for cultivation with temperature and humidity control, through the production of inoculum, described in chapter 1, elaboration of a main substrate and supplementation, according to chapter 2, at the end, perform the bromatological analysis of the fruiting bodies, in chapter 3. In mushroom cultivation, the first step is the production of spawns or “seeds”. The production of matrix or mycelium has the same technique of inoculation of cereal grains and recommendations for different species. The choice of grain-based substrates may vary according to the region, and will depend on the local supply, aiming at making the process cheaper. Grains of Sorghum bicolor L. Moench and Zea mays L. were chosen for research because they are easy to acquire and have affordable prices. The inoculum used to colonize the cereals was provided by the Laboratory of Bioactive Compounds (LACOMBI), which was subcultured on dextrose potato agar (DPA). Sorghum showed better performance than corn, but both are viable for spawn production. For the production of mushrooms, gueroba straw - Syagrus oleracea was used as substrate, and supplementation made with jatobá pulp - Hymenaea courbaril L, flour from the peel of the pequi Caryocar brasiliense Camb. and mature compost. Bags with 600g of ground straw were assembled and supplementation was carried out at 10, 20 and 30% of dry weight of the gueroba. The composition of macro and micronutrients showed a rich diversity. The use of additives to the substrate did not contribute to the increase in Biological Efficiency, reaching a maximum of 33.93%, verified in the use of pure gueroba residue. Maximum productivity (11.36%) was found using gueroba substrate supplemented with 10% jatobá pulp. The harvested fructifications were sent to the Federal Technological University of Parana – UTFPR, for chemical analysis. Were detected that the mushrooms had phenolic compounds (CF) in their composition, the basidiomes cultivated in the gueroba substrate with 10% supplementation of pequi peel flour presented 74 mg AGE/g, the highest amount among the other fruiting bodies cultivated in the other substrates.